Incidence and Treatment Trends of Symptomatic Discoid Lateral Menisci: An 18-Year Population-Based Study - Sabbag, Orlando D. (Orthop J Sports Med, 2018)
BACKGROUND: A symptomatic discoid lateral meniscus is an uncommon orthopaedic abnormality, and the majority of information in the literature is limited to small case series. PURPOSE/HYPOTHESIS: The purpose of this study was to determine the incidence of symptomatic discoid menisci in a geographically determined population and to describe treatment trends over time. The hypothesis was that the incidence of symptomatic discoid menisci would be highest among adolescent patients, and thus, the rate of surgical treatment would be high compared with nonoperative treatment. STUDY DESIGN: Descriptive epidemiology study. METHODS: The study population included 79 patients in Olmsted County, Minnesota, identified through a geographic database, who were diagnosed with a symptomatic discoid lateral meniscus between 1998 and 2015. The complete medical records were reviewed to confirm the diagnosis and evaluate the details of injury and treatment. Age- and sex-specific incidence rates were calculated and adjusted to the 2010 United States population. RESULTS: The overall annual incidence of symptomatic discoid lateral menisci was 3.2 (95% CI, 2.5-3.9) per 100,000 person-years; 12.6% of the patients in the cohort had bilateral symptomatic discoid lateral menisci. The overall annual incidence was similar between male (3.5 per 100,000 person-years) and female patients (2.8 per 100,000 person-years). The highest incidence of symptomatic discoid lateral menisci was noted in adolescent male patients aged 15-18 years (18.8 per 100,000 person-years). A majority (72.2%) of patients presented with a symptomatic tear of the discoid meniscus. The remaining patients presented with mechanical symptoms, including catching/locking or effusion, with no demonstrable meniscus tear on imaging or diagnostic arthroscopic surgery. Additionally, 20.0% of patients were observed to have peripheral instability of the meniscus at the time of diagnostic arthroscopic surgery. The mean age of those with peripheral instability was significantly younger than of those who did not have peripheral instability. Sixty patients (75.9%) received surgical treatment during the study period, including 49 (81.7%) patients who underwent partial lateral meniscectomy and 11 (18.3%) patients who underwent lateral meniscus repair in addition to saucerization. CONCLUSION: With an overall annual incidence of 3.2 per 100,000 person-years, a symptomatic discoid meniscus is an uncommonly encountered orthopaedic abnormality. However, the incidence of symptomatic discoid lateral menisci is highest in adolescent male patients. Because of the high rate of meniscus tears in patients presenting with symptoms, the majority are treated surgically.